Financial health and well-being of rural female caregivers of older adults with chronic illnesses - Nasreen Lalani; Evans Appiah Osei; Siqi Yang; Bhagyashree Katare; Sampada Wagle (BMC Geriatrics)
Abstract Background Rural caregivers experience significant financial stressors while caring for their older family members with chronic illnesses. Limited access to care, support, and resources in rural areas poses significant financial threats and insecurity for some caregivers. As the majority of rural family caregivers are women, these challenges also represent gender disparities, role imbalances, and division of labor in the society that has rarely been explored in the literature from a rural context. To address these gaps, our study aims to explore the lived experiences of financial burdens and struggles of rural female family caregivers of older adults with chronic illness. Method Using a purposive sampling approach, qualitative interviews among N = 20 rural woman caregivers of older adults with any serious chronic illness was carried out. Interviews were done in-person, telephone or online as preferred by the participants. Each interview was about 45–60 min. All the data were recorded, transcribed, and analyzed using the thematic content analysis approach. Results Our findings showed significant gender role imbalances and financial disparities among the rural women caregivers. Major themes identified were indirect caregiving costs, direct caregiving costs, and barriers in navigating financial support systems. Participants reported losing jobs, experiencing caregiving stress and poor wellbeing, time constraints, financial losses, using pension plan and health coverage benefits to support themselves and their family. Barriers reported include financial decision making and documentation struggles, and difficulties in accessing savings and health coverage benefits and other legal complications. Conclusion Rural female caregivers face significant financial threats and insecurities exacerbated by the interplay of gender roles and rural inequities. These inequities need to be addressed to support better caregiving policies and interventions. Provision of financial services and guidance to support rural and disadvantaged women family caregivers in navigating financial resources, financial health planning and decision-making processes is needed. Future comparative and longitudinal studies are recommended to see the long-term effects of financial burdens and inequities on the wellbeing of female caregivers of older adults in the rural communities.